TESTING FOR “RANDOMNESS” IN SPATIAL POINT PATTERNS, USING TEST STATISTICS BASED ON ONE-DIMENSIONAL INTER-EVENT DISTANCES (Journal of Sciences, Islamic Republic of Iran)
To test for “randomness” in spatial point patterns, we propose two test statistics that are obtained by “reducing” two-dimensional point patterns to the one-dimensional one. Also the exact and asymptotic distribution of these statistics are drawn.